In Pursuit of Religious Freedom Bishop Martin Stephan's Journey. - Stephan, Philip (Lanham : Lexington Books, 2008)
In Pursuit of Religious Freedom tells the story of Martin Stephan, a religious leaders whose leadership, vision, and courage stemmed from a fifteenth-century ancestry grounded in the reformations of John Huss and Martin Luther. Like previous Stephan generations, Martin fled religious intolerance for freedom of worship. As an adult, his deep-rooted faith and moral values were threatened when he was confronted with family, social, and spiritual crises.
Appendix D: Regulations for Settlement of the Lutheran ""Gesellschaft"" Emigrating with Herr Pastor Stephan to the United States of North AmericaAppendix E: Martin Stephan's Investiture as Bishop on Board the GIbers, January 14, 1839; Appendix F: Excerpts of the ""Exultanten-Lieder auf dem Meere, "" Songs of Exiles on the Sea, by O.H. Walther; Bibliography; Index; About the Author.
Description based on print version record.
Keywords: Lutheran Church -- Missouri Synod -- Bishops -- Biography; Lutherans -- Missouri -- History -- 19th century; Missouri -- Church history -- 19th century; Saxons -- Missouri -- History -- 19th century; Stephan, Martin, 1777-1846.; Stephan, Martin, -- 1777-1846.; Lutheran Church--Missouri Synod -- Bishops -- Biography; Lutherans -- Missouri -- History -- 19th century; Saxons -- Missouri -- History -- 19th century; Missouri -- Church history -- 19th century; RELIGION / Christianity / Protestant; Electronic books